If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1x + 4 = 2 Reorder the terms: 9 + 4 + -1x = 2 Combine like terms: 9 + 4 = 13 13 + -1x = 2 Solving 13 + -1x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -1x = 2 + -13 Combine like terms: 13 + -13 = 0 0 + -1x = 2 + -13 -1x = 2 + -13 Combine like terms: 2 + -13 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| 5x-7x-7=2x+5-7 | | D^2=13x | | (3x+14)=(5x+20) | | -14+5k=k-3k | | 3m+6+6=m-18 | | -99=-3(3x+7)-6 | | 2(s-6)=4 | | 9y-y=-14+y | | (2x)+16=48 | | C+c+3=53 | | (8x+5)+(4x-5)=180 | | 2(-5)+y=6 | | C-7=5.3 | | 15-2/3x=9 | | y-9=6/7(x-4) | | ln(a+10)+5=7 | | (1-3)x+5=6x+-8 | | 2x+5+3x+10=100 | | 3.5h=2h-12 | | 10(4x+2)=3(8-x)+6 | | 8x+5+4x-5=180 | | y-9=6/7)x-4) | | 0.83t^2-10t+31=0 | | 2n+11=10 | | -14=7(y-5) | | -2=7-v | | 7-2a=54 | | 10+e-5+e=5(e-1) | | -7/2-3/7x=-8/3 | | 4x^2=-28x | | 3(u+6)=7u | | 9y-8y=12 |